Vulvar cancer management and wrangling recurrent disease: A report from the society of gynecologic oncology journal club - Jessica E. Parker; Emi J. Yoshida; Lilian T. Gien; Brian M. Slomovitz; Christa Nagel (Gynecologic Oncology Reports, 2023)
The Society of Gynecologic Oncology (SGO) Journal Club webinar series is an open forum that invites national experts to discuss the literature pertaining to important topics in the management of gynecologic cancers. On August 14th, 2023, SGO hosted a journal club focused on the management of upfront and recurrent vulvar cancer. Our discussants included Dr. Brian M Slomovitz from Mount Sinai Medical Center in Miami Beach, Dr. Emi Yoshida from the University of California San Francisco Helen Diller Family Comprehensive Cancer Center, and Dr. Lilian Gien from the University of Toronto Sunnybrook Odette Cancer Center. During the discussion,we reviewed the progression of vulvar cancer surgery from en bloc resection of the vulva and groins, to partial radical vulvectomy and sentinel lymph nodes. We also reviewed the management of node positive vulvar cancer including published and accruing Groningen International Study on Sentinel Nodes in Vulvar Cancer (GROINSS) trials and other sentinel trials from the Gynecologic Oncology Group (GOG). Here we will also review the literature on the management of recurrent vulvar cancer, highlighting current treatment options and ongoing clinical trials. The following is a report of the journal club presentation.